Nickel oxide nanostructured electrodes towards perylenediimide-based dye-sensitized solar cells - Feihl, Sebastian; Costa Riquelme, Rubén Dario; Pflock, Stephan; Schmidt, Cordula; Schönamsgruber, Jörg; Backes, Susanne; Hirsch, Andreas; Guldi, Dirk Michael (RSC Advances, 2012)
In this work, we have realized nickel oxide (NiO) electrodes that serve as photocathodes in p-type dye-sensitized solar cells (p-DSSCs) sensitized by dendronized perylenediimides (PDIs). To this end, two different approaches in terms of preparing NiO nanoparticle pastes were pursued to fabricate mesoporous electrodes on conductive fluorine doped tin oxide (FTO) glass substrates. Firstly, commercially available NiO nanoparticles were dispersed in a mixture of ethanol and terpineol. Here, in order to obtain a mesoporous network two types of ethylcelluloses (EC), that is, EC 5-15 and 30-50 mPa s, were added in 1:1 weight ratios. Following the evaporation of ethanol, the resulting pastes were spread on FTOs by doctor blading and calcinated at different temperatures. Importantly, the calcination temperature evolved as a crucial aspect in developing efficient electrodes. Nevertheless, the visual appearance of these NiO electrodes prompts a fairly heterogeneous coverage. To circumvent the aforementioned problem, a second approach en route to homogenous electrodes was investigated. In that particular case, commercial NiO nanoparticles were mixed with a mixture of EC 5-15 and 30-50 mPa s at a 1:1 weight ratio, with triacetin as a plasticizer in ethanol. In doing so, pastes containing 7 wt% EC, 3 wt% triacetin, and 3 to 20 wt% NiO nanoparticles were prepared. Most importantly, scanning electron microscopy (SEM) images corroborated the fact that the resulting electrodes revealed a dense coverage on FTOs. In addition, further characterizations ranging from UV/Vis transmission spectroscopy and conductivity measurements to Barrett-Joyner-Halenda (BJH) pore size and volume analysis were carried out. In the final step, the applicability of the new NiO photoelectrodes for p-DSSCs was successfully demonstrated by utilizing two types of PDIs, namely a symmetric 1 and a non-symmetric dendronized 2. Key aspects such as time dependence of dye uptake, hole lifetime and resistance features of the electrodes under operation conditions were investigated. © 2012 The Royal Society of Chemistry.